NahK/NahL: estrutura, função e mecanismo de ação de um complexo macromolecular - Samuel Leite Guimarães (2015)
Naphthalene is a toxic and well-studied polycyclic aromatic hydrocarbon. Its degradation by the bacterium Pseudomonas putida G7 is the focus of numerous studies. In this organism, the enzymes NahK (4-oxalocrotonate decarboxylase, 28.4 kDa) and NahL (vinylpyruvate hydratase, 27.9 kDa) belong to the lower pathway of naphthalene degradation. They exist in vivo as a protein complex, catalyzing an interesting sequence of reactions with an unstable intermediate that raises a number of mechanistic and structural questions. Our aim was to characterize kinetically and structurally the enzymes NahK, NahL and their complex. The nahK and nahL genes were subcloned separately into pET28a-TEV vector for expression, and also subcloned together into pETDuet-1 vector for co-expression in Escherichia coli BL21(DE3) cells. NahK and its complex with NahL were purified by Immobilized Metal Ion Affinity and Size-Exclusion Chromatographies. The protein samples were analyzed by Dynamic Light Scattering, Circular Dichroism, and the steady-state kinetic parameters for their natural substrates were obtained. The NahK/NahL complex was also analyzed by Small-Angle X-Ray Scattering. NahK and NahK/NahL samples in their apo or ligated forms with different substrate analogues were crystallized and X-Ray Diffraction data were collected. NahK expressed alone and co-expressed with NahL was purified to homogeneity and both enzymes shown a kcat/KM values up to 107 M-1s-1. The crystalline structures of NahK in apo and ligated forms with Mg2+ and substrate analogues allowed the proposition of a reaction mechanism involving a lid domain. SAXS measurements suggested a particle of 275 kDa for the NahK/NahL complex, and the crystalline structure of this complex suggested a heterodecamer assembly. NahK and NahL face their active site cavities to each other in a large, elegant and functional quaternary structure. Together, these enzymes perform important steps during naphthalene degradation in P. putida G7. This work provided a deep structural and functional knowledge of this interesting protein complex.